2009
DOI: 10.1017/s0267190509090126
|View full text |Cite
|
Sign up to set email alerts
|

The Workplace, the Society and the Wider World: The Offshoring and Outsourcing Industry

Abstract: Workplace language assessment poses special issues for language testers, but also, when it becomes very large scale, it poses issues for language policy. This article looks at these issues, focusing on the offshore and outsourcing (O&O) industry as it is transitioning from native-speaking (NS) countries into nonnative-speaking (NNS) destinations such as India and the Philippines. This is obviously most impacted in call centers, where the ability of customer service representatives (CSRs) to communicate wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 14 publications
(18 reference statements)
0
9
0
Order By: Relevance
“…Call centers are a currently expanding domain where English is demanded (e.g., Friginal, 2007;Rahman, 2009). Hamp-Lyons and Lockwood (2009), who made a needs analysis of call centers in the Philippines, found that outsourced call centers complain of very poor recruitment because of poor English language ability. Herat and McLoughlin (2010) analyzed 330 advertisements for jobs in the commercial sector in Sri Lanka.…”
Section: Workplaces In the English Outer And Expanding Circles In Asiamentioning
confidence: 99%
“…Call centers are a currently expanding domain where English is demanded (e.g., Friginal, 2007;Rahman, 2009). Hamp-Lyons and Lockwood (2009), who made a needs analysis of call centers in the Philippines, found that outsourced call centers complain of very poor recruitment because of poor English language ability. Herat and McLoughlin (2010) analyzed 330 advertisements for jobs in the commercial sector in Sri Lanka.…”
Section: Workplaces In the English Outer And Expanding Circles In Asiamentioning
confidence: 99%
“…Previous research into outsourced business processing outsourcing (BPO) call centre interaction (Forey and Lockwood ; Friginal ; Lockwood et al , Hamp‐Lyons & Lockwood , Lockwood ) has shown that many communication difficulties occur where native speaker customers talk to non‐native speaker agents in such BPO worksites in the Philippines and in India. There are onshore political and business concerns around outsourced call centres resulting in the agents requiring extremely high levels of English and the language training this industry provides aims for native‐speaker norms.…”
Section: Resultsmentioning
confidence: 99%
“…They are integral to the workplace, but they are shaped by factors such as a company's external and internal environments, which in turn influence management approaches and modes of work organization [38,39,42]. Within the workplace, oral communication is influenced by the status of the parties, the purpose of communication, and the medium [44].…”
Section: Public Speaking As a Workplace Basic Skillmentioning
confidence: 99%
“…Nevertheless, it is claimed that, in the context of English as a global language of international business, multinational corporations find ways of matching the authentic workplace requirements with non-English background preparation [42]. Moreover, according to Bhatia and Bremner [41], dissatisfaction from the side of the student is strong, as most learners need support both in English for Academic purposes and in English for the workplace: the perception of business teachers generally reinforce and complement this statement.…”
Section: Business Workplace Requirements and Esp Practicementioning
confidence: 99%